ANALYSIS OF TRENDS IN THE USE OF MODERN FISCAL INSTRUMENTS TO ENSURE THE EFFECTIVENESS OF TAX EVASION REDUCTION MECHANISMS (Academicia Globe: Inderscience Research, 2024)
This article describes large reforms aimed at creating favorable conditions.